PERSEPI MASYARAKAT TENTANG PERUSAHAAN AIR MINUM DAERAH (PDAM) DI NAGARI KAPELGAM KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Rozes, Zulvia - (Pendidikan Geografi, 2014)
The purpose of this research to know: 1) The Public perception about the service of PDAM water in Nagari Kapelgam, Bayang, Kabupaten Pesisir Selatan. 2) Public perception of the running well of the PDAM water in Nagari Kapelgam, Bayang, Kabupaten Pesisir Selatan. 3) Public perception about the governments efforts in providing of water suppl in Nagari Kapelgam Bayang, Kabupaten Pesisir Selatan. The population in this study were all the people who used the PDAM with the numbered 240 families. And the sample of this research were amounted to 96 respondents. The technique of data analysis in this research was used Descriptive analysis. The results of data analysis showed that the result of achievement in each indicator was: the indicator of the PDAM officer service toward significant of public influanced and positive influence toward the public perception in Nagari Kapelgam Bayang, Kabupaten Pesisir Selatan. Smoothness indicators was significant and positive influence toward the public perception in Nagari Kapelgam Bayang, Kabupaten Pesisir Selatan and then the subsequent government efforts in providing of indicator of PDAM water was a significant effect and positive effect toward public perception in Nagari Kapelgam Bayang, Kabupaten Pesisir Selatan.